A variante de Barzilai-Borwein do método gradiente - Moura, Abssan Matuzinhos de (2016)
The gradient method is a classical optimization methods to minimize a function. This method deserves special mention for its simplicity and easy understanding. This work is based on the study of the gradient method with step size given by the variant Barzilai- Borwein. Our goal is to present the convergence of the method with this variant. First we will study the two-dimensional case, for strictly convex quadratic functions. In this case, besides obtaining the convergence of the method, we see that such convergence occurs with R-superlinear rate. In the final part of the work, we will study the method with the variant Barzilai-Borwein not necessarily quadratic functions, concluding that the method converges.